2022
DOI: 10.3390/cancers14215402
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as the Best Supportive Care in Cancer: The Clinician’s and the Researcher’s Perspectives

Abstract: Multidisciplinary supportive care, integrating the dimensions of exercise alongside oncological treatments, is now regarded as a new paradigm to improve patient survival and quality of life. Its impact is important on the factors that control tumor development, such as the immune system, inflammation, tissue perfusion, hypoxia, insulin resistance, metabolism, glucocorticoid levels, and cachexia. An increasing amount of research has been published in the last years on the effects of physical activity within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 351 publications
0
13
0
1
Order By: Relevance
“…For instance, the treatment with the common immunosuppressant rapamycin has sex-specific effects [15], highlighting the importance of taking into account sex differences for precision medicine. The same is true for physical exercise [205] as an intervention against cancer. The conclusion of a ponderous survey on the effectiveness, acceptability, and safety of exercise for cancer cachexia in adults is that "further high-quality randomized controlled trials are still required to test exercise alone or as part of a multimodal intervention to improve people's well-being throughout all phases of cancer care", suggesting that additional clinical and basic studies are needed to implement exercise efficacy [206].…”
Section: Which Direction Shall We Go?mentioning
confidence: 88%
“…For instance, the treatment with the common immunosuppressant rapamycin has sex-specific effects [15], highlighting the importance of taking into account sex differences for precision medicine. The same is true for physical exercise [205] as an intervention against cancer. The conclusion of a ponderous survey on the effectiveness, acceptability, and safety of exercise for cancer cachexia in adults is that "further high-quality randomized controlled trials are still required to test exercise alone or as part of a multimodal intervention to improve people's well-being throughout all phases of cancer care", suggesting that additional clinical and basic studies are needed to implement exercise efficacy [206].…”
Section: Which Direction Shall We Go?mentioning
confidence: 88%
“…One of exercise’s primary effects is a decrease in plasma concentrations of the hormone estrogen. Inducing cell proliferation and progression, blocking apoptosis, and promoting angiogenesis are all ways in which estrogens promote breast carcinogenesis [ 32 ]. Several studies have revealed that menopausal women who engage in regular exercise have lower levels of free estrogen in their blood [ 33 , 34 , 35 ].…”
Section: Physical Activity and Cancermentioning
confidence: 99%
“…Neben den tumorpräventiven Effekten von regelmäßiger körperlicher Aktivität, die gut erforscht und anerkannt sind [47], gibt es aber auch eine stetig wachsende Evidenz für die wichtige Rolle von Sport und Bewegung innerhalb der multimodalen Tumortherapie. Denn während vor noch wenigen Jahren bei einer Krebserkrankung in der Regel strikte körperliche Schonung empfohlen wurde, zählt die Sportund Bewegungstherapie heute als eine der wichtigsten Supportivmaßnahmen in der onkologischen Komplementärtherapie [48].…”
Section: Die Synergie Von Bewegung Und Ernährung In Der Therapie Von ...unclassified